Solar Tracker - Hashim, Irfan Danial; Ismail, Ammar Asyraf; Azizi, Muhammad Arief (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2020)
The generation of power from the reduction of fossil fuels is the biggest challenge for the next half century. The idea of converting solar energy into electrical energy using photovoltaic panels holds its place in the front row compared to other renewable sources. But the continuous change in the relative angle of the sun with reference to the earth reduces the watts delivered by solar panel. Conventional solar panel, fixed with a certain angle, limits their area of exposure from the sun due to rotation of the earth. Output of the solar cells depends on the intensity of the sun and the angle of incidence. To solve this problem, an automatic solar cell is needed, where the Solar Tracker will track the motion of the sun across the sky to ensure that the maximum amount of sunlight strikes the panels throughout the day. By using Light Dependent Resistors, it will navigate the solar panel to get the best angle of exposure of light from the sun.